Criminal Justice System Processing and Victimization: Results from a Longitudinal Study of Males and Females - Adlet, Yergali (Victims & offenders, 2023)
There has been a great deal of interest in understanding the etiological underpinnings to victimization. This body of research has uncovered a list of risk factors that have been consistently tied to victimization. One of the more consistent results is that criminal offenders are at-risk for being victimized. The current study expanded on this finding by examining whether four measures of being processed through the criminal justice system (i.e., arrest, conviction, probation, and incarceration) were related to multiple measures of victimization in adolescence and adulthood. To do so, data from the National Longitudinal Study of Adolescent to Adult Health (Add Health) were analyzed. The results revealed consistent and statistically significant associations between the criminal justice processing variables and the victimization measures for both males and females even after controlling for self-reported criminal and delinquent involvement. We conclude by contextualizing the results and offering suggestions for future research in this area.